Review of Internal Radiocarpal Distraction Plating for Distal Radius Fracture Fixation. (January 2020) - Vakhshori, Venus; Alluri, Ram Kiran; Stevanovic, Milan; Ghiassi, Alidad
Internal radiocarpal distraction plating is a versatile tool in the treatment of distal radius fractures that are not amenable to nonoperative treatment or operative fixation with standard volar or dorsal implants. Internal distraction plates may also be indicated in the setting of polytrauma or osteopenic bone. The plate functions as an internal fixator, using ligamentotaxis to restore length and alignment while providing relative stability for bony healing. The plate can be fixed to either the second or the third metacarpal, and anatomic and biomechanical studies have assessed the strengths and weaknesses of each strategy. This operative fixation technique leads to acceptable radiographic results and functional outcomes. Following fracture union, the plate is removed, and wrist range of motion is resumed.